Navigating University Life: A Qualitative Study of Social and Academic Challenges and Coping Strategies Among Introvert Students in Higher Education - Shahzadi, Shazia; Munir, Naureen; Ullah, Naqeeb; Mahar, Abdul Qayoom; Mahar, Sourath (2024)
This qualitative study investigated the social and academic challenges encountered by introvert university students, aiming to deepen the understanding of their distinct experiences. Through in-depth, semi-structured interviews with 12 undergraduate students from Foundation University in Rawalpindi, the study identified key challenges faced by introverts. Participants expressed that social anxiety, particularly in group discussions and public speaking, led to discomfort and avoidance of activities that interfered with their academic performance. The findings indicated issues related to academic support and social interactions, often resulting in negative self-perceptions and feelings of isolation. Students reported difficulties in connecting with peers, which impacted their engagement with the learning process. Nonetheless, the results revealed that introvert students employed various coping strategies, such as seeking solitude for reflection, utilizing learning environments effectively, and seeking assistance from peer sand instructors. The study under scored the necessity for educational institutions to accommodate the diverse needs of introvert students through integrated teaching methods and tailored support programs.